Diagnosis, Treatment, and Management for Chronic Coronary Syndrome: A Systematic Review of Clinical Practice Guidelines and Consensus Statements - Tianyue Jing; Yu Wang; Yukun Li; Liangyu Cui; Xingfang Liu; Dasheng Liu; Cong Ren; Tong Yin; Zhiwei Zhao; Jiaheng Wang; Xuejie Han; Liying Wang (International Journal of Clinical Practice)
Objectives. Management of chronic coronary syndrome (CCS) encompasses a broad spectrum of practices, posing considerable complexity and variability. While guidelines have been established to augment the management quality of CCS, notable disparities persist across their recommendations. This study strives to scrutinize, compare, and reconcile these guideline recommendations pertaining to the diagnosis, treatment, and management of CCS patients. Our goal is to align these recommendations with contemporary clinical practices, thus laying a robust foundation for their pragmatic application in clinical settings. Methods. A comprehensive systematic search was conducted across multiple databases, including PubMed, EMBASE, China National Knowledge Infrastructure, Wanfang Database, China Science and Technology Journal Database, Chinese Biomedical Literature Service System, Chinese Science and Technology Periodical Database, and Chinese Biological Medicine Database. The timeframe for this search spanned from their inception up to May 30, 2022, aiming to collate all published guidelines relevant to CCS. Subsequently, two independent reviewers undertook the task of appraising the quality of these guidelines by utilizing the Appraisal of Guidelines for Research and Evaluation II instrument. Results. The search yielded a total of 10,699 citations. Following a thorough evaluation, fourteen clinical practice guidelines and four consensus statements, each offering specific recommendations for CCS, were selected. The quality of these guidelines showcased a broad spectrum of variation. The domain of “presentation clarity” received the highest accolades, while “applicability” languished at the lower end of the scoring spectrum. On average, the guidelines attained a quality score denoting sufficiency. Furthermore, recommendations across different guidelines for the diagnosis, treatment, and management of CCS displayed a striking level of divergence. Conclusion. The landscape of published CCS guidelines is marked by extensive variations in scope, quality, and recommendations. Hence, there is a compelling need for collaborative efforts amongst multidisciplinary professionals to forge comprehensive, higher-quality evidence-based guidelines; such a concerted approach is paramount to enhance treatment efficacy and health outcomes for patients grappling with CCS.